THE INFLUENCE OF BRAIN GYM (CECILIA KOESTER) ON THE DEVELOPMENT OF FINE MOTORCY IN CHILDREN AGED 4-6 YEARS - Ainun Jariyah, Mega Ayu; Mianti Nurrizky Sutejo; Addini, Ragil Aidil Fitriasari (STIKES Telogorejo Semarang, 2024)
Abstract Background: The World Health Organization (WHO) reports that 5% to 25% of preschool-aged children worldwide experience minor brain dysfunctions, including fine motor skill disorders. Partial and total motor development disorders are reported in approximately 0.4 million (16%) children in Indonesia. This is supported by a study conducted by 31 children aged 4-6 years at the Talitakum Kudus School and Therapy experienced acceptable motor delays. The impact of delays in fine motor skills can affect a child's development, especially activities and skills that use their hands and fingers, which will be related to daily activities. Proper stimulation can be given to children who experience delays in their fine motor skills by providing brain gym exercises. Objective: To determine the effect of a brain gym on fine motor development in children aged 4-6 years. Method: This research uses a quasi-experimental research design and a pre- and post-test one-group design research design. The respondents in this study were 31 children using a purposive sampling technique. Brain gym exercises were carried out for four weeks, three times a week, for 30 minutes. The instrument in this study used the Denver Development Screening Test (DDST) to measure aspects of children's fine motor development before and after treatment. Results: The Wilcoxon results before and after treatment obtained a p-value of 0.000; this means the p-value < 0.05, which means Ha is acceptable; therefore, the results of the hypothesis test state that there is an effect of giving brain gym before and after treatment. Conclusion: The brain gym (Cecilia Koester) influences the fine motor development of children aged 4-6 years